2021
DOI: 10.1093/jpepsy/jsab089
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Self-Reported Psychological Impacts of COVID-19: Associations With Parental Burnout, Child Behavior, and Income

Abstract: Objective The current study investigates associations between parents’ perceived coronavirus disease 2019 (COVID-19) psychological impacts and experiences of parental burnout, children’s behaviors, and income. Methods Data were collected during an online survey of parents’ ( N = 1000) pandemic experiences in April 2020. Parents ( M = 36.5 years old, SD = 6.0; 82.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 37 publications
(46 reference statements)
5
49
0
1
Order By: Relevance
“…Caregivers must be well-supported and feel connected in order to be perceived by their children as emotional and instrumental support ( Kenigsberg et al, 2016 ), and children's negative perceptions of parental neglect and control are correlated with an increased risk of subsequent diagnosis of psychiatric disorders ( Young et al, 2011 ). Given the dynamic interplay between caregiver distress and child well-being ( Babore et al, 2021 ; Bate et al, 2021 ; Kerr et al, 2021 ; Vaterlaus et al, 2021 ), policies and programs that aim to improve children's mental and behavioral health should include family-based therapies that address caregiver stress and promote mental health of the family, rather than treat children in isolation. The complex systems in which children interact including their family environments and further layered social, built, and natural environments can be leveraged to foster multisystemic resilience ( Ungar & Theron, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Caregivers must be well-supported and feel connected in order to be perceived by their children as emotional and instrumental support ( Kenigsberg et al, 2016 ), and children's negative perceptions of parental neglect and control are correlated with an increased risk of subsequent diagnosis of psychiatric disorders ( Young et al, 2011 ). Given the dynamic interplay between caregiver distress and child well-being ( Babore et al, 2021 ; Bate et al, 2021 ; Kerr et al, 2021 ; Vaterlaus et al, 2021 ), policies and programs that aim to improve children's mental and behavioral health should include family-based therapies that address caregiver stress and promote mental health of the family, rather than treat children in isolation. The complex systems in which children interact including their family environments and further layered social, built, and natural environments can be leveraged to foster multisystemic resilience ( Ungar & Theron, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the COVID-19 pandemic, families face increased financial strain and decreased support, especially as business closures threaten job security, stay-at-home orders limit social activity and connection, and school closures place an increased childcare and education burden on parents. In particular, family physical and mental health concerns, homeschooling challenges, economic stress, marital conflicts, and intensified parent-child relationships uniquely impact those serving in caregiver roles during COVID-19 ( Kerr et al, 2021 ; Wu & Xu, 2020 ). In addition, disruptions to work and learning and changes to social and daily personal care routines are heightened for caregivers ( Park et al, 2020 ; Russell et al, 2020 ), which can lead to increased caregiver stress and spillover effects to others in the family, particularly children ( Curtis et al, 2000 ; Nelson et al, 2009 ; Seddighi et al, 2021 ; Wood et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, evidence suggests that stress and mental health struggles may have been uniquely exacerbated for parents [ 29 , 30 ] and children [31] , [32] , [33] . Parents, especially mothers [34] [35] , have assumed additional child care and schooling responsibilities [ 3 , 36 ], resulting in increased parenting-related exhaustion and decreased parental resilience [ 37 , 38 ]. For some families, the pandemic has highlighted or altered relations within co-parenting partnerships, by increasing or otherwise altering the time that partners spend together parenting their children, and/or foregrounding unequal or sub-optimal dynamics around caregiving responsibilities from one or both partner's perspective [39] .…”
Section: Introductionmentioning
confidence: 99%
“…Heightened stress generated by COVID-19 may impact parents’ ability to effectively parent and provide childcare ( Connell & Strambler, 2021 ; Janssen et al, 2020 ; Russell, Hutchinson, Tambling, Tomkunas, & Horton, 2020 ), therefore posing a risk to children’s well-being and creating an increased risk of maltreatment ( Font, 2021 ; Nguyen, 2021 ). COVID-19–related studies have reported an increase in mental health problems, such as anxiety and stress ( Bate et al, 2021 ; Bean et al, 2021 ; Caldwell et al, 2020 ; Gayatri & Irawaty, 2021 ; Huang & Ougrin, 2021 ; Kerr, Fanning, Huynh, Botto, & Kim, 2021 ; McFadden et al, 2021 ; de Winter, de Winter, Bollati, & Milani, 2020 ; Wu & Xu, 2020 ). Parenting stress is heightened, particularly in already at-risk families ( Becker et al, 2020 ; Bik-Multanowska, Mikocka-Walus, Fernando, & Westrupp, 2022 ; Miller, Cooley, & Mihalec-Adkins, 2020 ; Miller, Niu, & Moody, 2020 ; Sonnenschein, Stites, Grossman, & Galczyk, 2022 ; Valeriote & Milligan, 2021 ; Yael, Carmit-Noa, Roni, & Shirli, 2022 ), and has been found to result from issues related to remote schooling and worries about health and children’s well-being ( Garbe et al, 2020 ; Goldberg et al, 2021a , 2021b , 2022 ; Wang et al, 2022 ).…”
mentioning
confidence: 99%